Quasiorthogonal projective spaces - Fryda, Jan (Annales Mathematicae Silesianae, 1992)
In the preceding paper (see [2]) we defined and investigated quasibilinear functionals on vector spaces, quasiorthogonal and weakly quasiorthogonal vector spaces. In the present paper we give certain applications of these concepts in projective geometry.